Dragon at the gates of Belmont: Obstacles to using Poland as a gateway for the rail component of the Belt and Road Initiative in light of geopolitical developments and shifting European Union policy towards China - Kociubiński , Jakub; Rae, Gavin (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
An important element of the Belt and Road Initiative (BRI) involves the construction of rail links between China and the European Union (EU). Despite the geopolitical fallout from the ongoing war in Ukraine, the route through Russia, Belarus, and onward to Poland presently constitutes the only viable overland route from China to the EU. In this context, this paper aims to answer the question of whether such actions by Member States may constitute a breach of obligations arising from membership in the European Union, and consequently whether EU law may pose an obstacle to the development of individual trade relations with China by Member States outside the institutional and legal framework of the Union. In this study, on the one hand, programme documents and EU law relevant to the issue presented were analysed, and on the other hand, the geopolitical and operational considerations of rail links between the EU and China were examined. The authors, being aware of the politicization of the subject, concluded that EU State aid law instruments could successfully be used to block infrastructure investments designed to facilitate the reception of Chinese freight traffic if such an impulse were to arise at the political level.